Analisis Penerapan Motivasi Kerja untuk Meningkatkan Kinerja Karyawan di Disporasu - Mei Fani, Mukhammad As Alukal Huda; Syarvina, Wahyu (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Work motivation and the work environment are important factors that affect employee performance. Work motivation is the internal energy that motivates a person to achieve their goals, while the work environment is an external factor that affects a person's motivation and performance. Therefore, it is very important to analyze the influence of work motivation and work environment on employee performance. This study was conducted using a qualitative approach. In qualitative methods, this research emphasizes an in-depth understanding of the phenomenon, involves interpretation of meaning, and explores subjective aspects. Through descriptive data collection, such as in-depth interviews, observation, or document analysis, this study aims to explore rich and contextual understanding. Work motivation has an important context involving various aspects that affect organizational dynamics. First of all, work motivation is strongly related to employee productivity. Employees who feel motivated tend to show higher levels of productivity, resulting in better performance and positive contributions towards achieving organizational goals. The success of an organization lies not only in the technical expertise of its employees but also in their level of motivation. Overall, work motivation is not just about providing a temporary boost but also about creating a foundation for long-term growth and the achievement of common goals. By combining recognition strategies, rewards, skills development, and career opportunities, organizations can create an environment that motivates, supports individual growth, and leads to collective success.